Organiza????o social: um modelo vi??vel a ser utilizado pelo Estado Nacional brasileiro na consecu????o de servi??os p??blicos sociais, face ??s exig??ncias de um mundo economicamente globalizado - Pereira J??nior, Antonio Alexandre (2015)
Organiza????es Sociais (OS) is a title that qualifies non-state non-profit entities, belonging to the (third sector), to receive public funds, property and even public servants, after the signature of the management contract, for achievement of social public services, in collaboration with the State. This indirect action model of the State was introduced to brazilian Law by Law No. 9637/98, during the second government of President Fernando Henrique Cardoso, with one of the measures disseminated in the Reform Plan of Public Administration, which had as its purpose the reduction of the size of public administration, the transformation of bureaucratic public administration in management, while encouraging the private sector to operate in newmarket niches. However, this model of state action in partnership with civil society, in protection of social rights, was labeled by the government's political opponents, as a way to circumvent the principles of public administration provided for in article 37 of the Brazilian Constitution. Therefore, this law was the subject of a direct action in the Supreme Court, the same year which went into effect. However the action was only judged by the Court on April 24, 2015, having related courtjudged partially valid action, just to give for the questioned articles, interpretation according to the Constitution. In view of the above, and because the OS have private nature, use the managerial administration, having employees with private working relationship, what enables the exemption of public administration, and consequently the reduction of public expenditure, this partnership model is consistent with the interests of a State that seeks to adapt to an economically globalized world.